Reducing Salmonella enterica serovar Enteritidis contamination in food: lytic bacteriophages in a homemade mayonnaise-like matrix - Consuelo Borie-Polanco (Universidad de Antioquia, 2020)
Background: Salmonella enterica serovar Enteritidis (SE) is one of the major causes of food-borne disease worldwide, mainly associated with the consumption of poultry products, such as eggs. Several control methods have been implemented in the egg production process, but they have not effectively reduced the outbreaks. Therefore, the use of bacteriophages for the biocontrol of food-borne pathogens is gaining increasing acceptance. Objective: To evaluate a bacteriophage cocktail's effectiveness in reducing SE counts in an experimentally contaminated mayonnaise-like matrix. Methods: Homemade mayonnaise was contaminated with SE (103 CFU/ml) with equal volume to a matrix (1:1) treated with a bacteriophage cocktail (five phages, MOI 105), and stored at 21 °C for 24 and 72 h. Bacterial counts were performed to evaluate the bio-controlling activity of the cocktail and compared with a contaminated but not treated group. Results: Significant reductions (up to 3.75 log10 CFU/ml) were observed in the bacteriophage-treated groups (p<0.0001). Conclusions: These results demonstrate the effectiveness of bacteriophages as biocontrol agents for Salmonella Enteritidis in a raw-egg-derivative foodstuff. Further studies are needed to prove the reduction in an undiluted homemade mayonnaise.